Compositional dependence of electrical conduction in solution grown Zn1-xCrxSe thin films: a correlation - Deshmukh, S. L.; Pingale, P. C.; Chavan, G. T.; Pawar, S. T.; Prakshale, V. M.; Kamble, S. S.; Jadkar, S. R.; Chaure, N. B.; Gopinath, C. S.; Maldar, N. N.; Deshmukh, L. P. (Journal of Materials Science: Materials in Electronics, 2017)
Zinc selenide (ZnSe) has a typical band gap of 2.7 eV suitable for window application and can easily be synthesized using a liquid phase chemical bath deposition. An attempt is made to tune its band gap and other characteristics to cope with a maxima of the solar spectrum by deliberate addition of Cr3+. ZnSe and Zn1-xCrxSe (0 <= x <= 0.35) thin films were obtained under the controlled deposition conditions (temperature = 70 A degrees C, time = 210 min, pH = 10, etc). The compositional analysis showed Zn2+ replacement by Cr3+. The X-ray photoelectron spectroscopy revealed chemical states of the constituents Zn, Cr and Se as 2(+), 3(+) and 2(-) respectively. The electrical conductivity and thermo-power measurements in the 300-550 K temperature range showed semiconducting nature of the material and that the electrical conduction is of the n-type. The electrical conductivity is found to be increased continuously up to x = 0.05 and then decreased for further increase in x. The Hall-probe measurements also confirmed n-type conduction. The average Hall coefficient for pure ZnSe is -1.03 x 10(7) cm(3)/C whereas, it is -4.55 x 10(6) cm(3)/C for a sample with x = 0.35.

Polymer-based hybrid catalyst of low Pt content for electrochemical hydrogen evolution - Chakrabartty, S. (International Journal of Hydrogen Energy, 2017)
Hydrogen is regarded as the most promising fuel to replace conventional fossil fuel. The electrochemical production of hydrogen requires catalyst and development of efficient non-Pt catalysts or catalysts with low Pt content are in demand. Herein, we demonstrate the photochemical synthesis of a hydrogen evolution electrocatalyst poly(α-terthiophene)-Pt nanoparticle hybrid material (polyTT-Pt) of low Pt content and its electrocatalytic activity. The synthesis of polyTT-Pt hybrid material involves the photoinduced electron transfer between α-terthiophene (α-TT) and and the subsequent in situ growth of polymer and Pt nanoparticles. The irradiation of the mixture of α-TT and with sunlamp initiates the oxidative polymerization and reduction of Pt complex to Pt nanoparticles. The polymer has cabbage-like microstructure and the in situ grown Pt nanoparticles have an average size of 1.8 nm. The Pt nanoparticles are embedded into the polymer matrix as well as randomly distributed over the polymer. The hybrid material contains 2.91 wt% of Pt and it shows characteristic electrochemical signature with an electrochemically active surface area of 35.7 m²/gPt. The hybrid material polyTT-Pt is electrocatalytically highly active though it contains very small amount of Pt. It efficiently catalyses hydrogen evolution reaction (HER) and the bench mark current density of 10 mA/cm² is achieved at an overpotential of 67 mV. The mass activity of the hybrid catalyst is 1172 mA/mgPt at the overpotential of 67 mV. The high activity is ascribed to the high electronic conductivity of the polymer matrix, facile access of electrolyte due to the embedded small nanoparticles and the presence of large number of catalytically active Pt sites. Tafel analysis suggests that the HER follows the Volmer-Tafel mechanism. Polymer-based hybrid catalyst of low Pt content for electrochemical hydrogen evolution. Available from: https://www.researchgate.net/publication/319039592_Polymer-based_hybrid_catalyst_of_low_Pt_content_for_electrochemical_hydrogen_evolution [accessed Oct 16 2017].

Direct thermal polymerization approach to N-rich holey carbon nitride nanosheets and their promising photocatalytic H-2 evolution and charge-storage activities - Antil, Bindu; Kumar, Lakshya; Reddy, K. P.; Gopinath, C. S.; Deka, Sasanka (ACS Sustainable Chemistry & Engineering, 2019)
Energy conversion and energy storage are two crucial challenges in green chemistry that have attracted tremendous attention for the last several decades. In this work, we have addressed both issues by synthesizing nitrogen-rich, few-layer-thick holey graphitic carbon nitride (g-C3N4) nanosheets by a simple, novel, direct thermal polymerization method, which is found to be very good in photocatalytic H-2 evolution reaction (energy-conversion) and charge-storage supercapacitor (energy-storage) applications. This as-synthesized conjugated polymer semiconductor (obtained stoichiometry C3N4.8) with unique structural and morphological advantages exhibits superior photocatalytic water splitting activity to H-2 evolution (2 620 mu mol h(-1) g(-1)) without the help of any cocatalysts under visible light in the presence of 20% triethanolamine (TEOA). The calculated apparent quantum yield is 8.5% at 427 nm, and the rate of photocatalytic hydrogen generation remained constant for nine consecutive catalytic cycles (9 h photocatalysis). The present material also shows electrochemical double layer capacitor (EDLC) behavior in alkaline electrolyte, where a symmetric coin cell device consisting of this electrode material without any large area support or conductive filler delivers high specific capacitance (275 F g(-1)), energy density (30 Wh kg(-1)), and power density (6651 W kg(-1)), and the supercapacitor cell can retain >98% capacitance efficiency up to 10 000 measured cycles at various current densities.
Keywords: g-C3N4; Hydrogen evolution; nanosheets; Photocatalyst; supercapacitor; water splitting